SCH79797 improves outcomes in experimental bacterial pneumonia by boosting neutrophil killing and direct antibiotic activity - Gupta, Naveen (J Antimicrob Chemother, 2018)
OBJECTIVES: The role of protease-activated receptor 1 (PAR1) in the pathogenesis of pneumonia and sepsis is ambiguous given the existing literature. As PAR1 is classically activated by the coagulation-based protease thrombin and leads to vascular leakage, our hypothesis was that PAR1 blockade with SCH79797 would be therapeutically beneficial in an experimental model of murine Gram-negative pneumonia. METHODS: In this study, we administered SCH79797 via the intrapulmonary route 6 h after the establishment of Escherichia coli pneumonia and observed a significant improvement in survival, lung injury, bacterial clearance and inflammation. We focused on neutrophils as a potential target of the PAR1 antagonist, since they are the predominant inflammatory cell type in the infected lung. RESULTS: Neutrophils appear to express PAR1 at low levels and the PAR1 antagonist SCH79797 enhanced neutrophil killing. Part of this effect may be explained by alterations in the generation of reactive oxygen species (ROS). SCH79797 also led to robust neutrophil extracellular trap (NET) generation and cathelicidin-related antimicrobial peptide (CRAMP) release by neutrophils. Surprisingly, SCH79797 also had a potent, direct antibiotic effect with disruption of the E. coli cell membrane. However, the newer-generation PAR1 antagonist, vorapaxar (SCH530348), had no appreciable effect on neutrophil activity or direct bacterial killing, which suggests the effects seen with SCH79797 may be PAR1 independent. CONCLUSIONS: In summary, we observed that intrapulmonary treatment with SCH79797 has significant therapeutic effects in a model of E. coli pneumonia that appear to be due, in part, to both neutrophil-stimulating and direct antibacterial effects of SCH79797.